Impact of Coronavirus Disease 2019 Pandemic on Pediatric Out-of-Hospital Cardiac Arrest in the Emergency Department - Chen, Chun-Yu; Lee, En-Pei; Chang, Yu-Jun; Yang, Wen-Chieh; Lin, Mao-Jen; Wu, Han-Ping (Frontiers in Pediatrics, 2022)
Background Out-of-hospital cardiac arrest (OHCA) in children is a critical condition with a poor prognosis. After the coronavirus disease 2019 (COVID-19) pandemic developed, the epidemiology and clinical characteristics of the pediatric emergency department (PED) visits have changed. This study aimed to analyze the impact of the COVID-19 pandemic on pediatric OHCA in the PED. Methods From January 2018 to September 2021, we retrospectively collected data of children (18 years or younger) with a definite diagnosis of OHCA admitted to the PED. Patient data studied included demographics, pre-/in-hospital information, treatment modalities; and outcomes of interest included sustained return of spontaneous circulation (SROSC) and survival to hospital-discharge (STHD). These were analyzed and compared between the periods before and after the COVID-19 pandemic. Results A total of 97 patients with OHCA (68 boys and 29 girls) sent to the PED were enrolled in our study. Sixty cases (61.9%) occurred in the pre-pandemic period and 37 during the pandemic. The most common age group was infants (40.2%) (p = 0.018). Asystole was the most predominant cardiac rhythm (72.2%, P = 0.048). Eighty patients (82.5%) were transferred by the emergency medical services, 62 (63.9%) gained SROSC, and 25 (25.8%) were STHD. During the COVID-19 pandemic, children with non-trauma OHCA had significantly shorter survival duration and prolonged EMS scene intervals (both p < 0.05). Conclusion During the COVID-19 pandemic, children with OHCA had a significantly lower rate of SROSC and STHD than that in the pre-pandemic period. The COVID-19 pandemic has changed the nature of PED visits and has affected factors related to ROSC and STHD in pediatric OHCA.